Efecto de bordes en ensayos de rendimiento en frijol (Phaseolus vulgaris L.) - Muñoz, J.E.; Amézquita, María Cristina; Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1977)
The simultaneous effect that lateral and end border rows may have on yield was studied in experimental plots at CIAT (Palmira, Colombia), using 25 black bean varieties in a 5 x 5 balanced lattice design with 6 replications. Plots measured 12 m(2) (6 rows, 4 m long). Unharvested end rows measured 0.5 m and lateral border rows were equal to 1 row on each side. Av yields of plots with 4 rows (unharvested lateral border rows) and 6 rows (complete plot) were 2551.8 and 2524.1 kg/ha, respectively, when end rows were not harvested. When end rows were harvested, yields were significantly higher (2890.2 and 2867.3 kg/ha, respectively; 0.01 less than P less than 0.0 5). The effect of the end rows was highly significant for varieties with the same growth habits because of the greater amount of light available at the borders. Neither lateral nor end/lateral border interactions were statistically significant. The effect of the end rows was consistent for all 25 varieties. (CIAT)